Karl Barth's Christological Treatment of Sin - Jorgenson, Allen G. (Scottish journal of theology, 2001)
A christological treatment of sin is, for Karl Barth, the only possibility for those who wish to know something of that which opposes life in Christ. Such a treatment must be christologically ordered in so far as Christ remains the arche, teloas, and nomos of theological thought. It is not coincidental, then, that his treatment of sin is proper to the doctrine of reconciliation and ordered by the christological assertion that Jesus Christ is truly God, truly human, and the unity of these as the ‘guarantor and witness of our atonement.’ Indeed, the knowledge of sin is only possible in the light of the revelation of God and humanity in the God-man Jesus Christ. Consequently, the doctrine of reconciliation is the proper place for the knowledge of sin in so far as Jesus, the one who knew no sin, was made to be sin ‘so that we might become the righteousness of God’ (2 Cor. 5:21). To know sin one must face the one who became sin for our sakes.